Gift from the gods? Dyslexia, popular culture and the ethics of representation - Kirby, P (Routledge, 2019)
The popular culture of learning difficulties has gained increasing attention in recent years, especially autism and Asperger syndrome. As yet, the representation of dyslexia has gone unexplored. Here, the popular culture of dyslexia is analysed, using the Percy Jackson series as a point of reference. It is suggested that three key tropes characterise these popular cultures: dyslexia as gift, functional limitation and joke. Conceptually, the article seeks to explore the potential for accounts of the popular culture of disability to go beyond the positive/negative ethical binary. It does so by situating representations of dyslexia within dyslexia’s broader histories and cultures, drawing on interviews with people with dyslexia from the UK Dyslexia Archive, amongst other sources. The article suggests that, in the case of dyslexia’s popular culture, the positive/negative ethical binary does not always capture the full complexity of representations.